Evaluating the capabilities of China's new satellite HJ-2 for monitoring chlorophyll a concentration in eutrophic lakes - Li, Jianzhong; Li, Yunmei; Yu, Yanhong; Li, Junda; Cai, Xiaolan; Lyu, Linze; Wang, Huaijing; Dong, Xianzhang; Song, Mengmeng; Zhu, Yuxin; Wang, Gaolun (International journal of applied earth observation and geoinformation, 2024)
•The performance of a new generation of Huanjing-2 CCD sensor has been evaluated.•A semi-empirical algorithm for Chla estimation was developed for eutrophic lakes.•CCD's high spatial resolution for detecting details was quantitatively evaluated.•Radiometric consistency between CCD and Sentinel-2/3 was assessed. HJ-2 (Huanjing-2) was launched in September 2020. It has a charge-coupled device (CCD) that offers a spatial resolution of 16 m and a revisiting time of two days, making it an excellent option for environmental and disaster monitoring. However, more evaluation is needed for the ability of CCD to monitor water quality. As chlorophyll a concentration (CChla) is the main indicator for water quality evaluation, in this study, the performance of the CCD sensor to monitor CChla has been verified, with a particular focus on typical eutrophic lakes. The essential findings can be summarized as follows: (1) the CCD sensor has a signal-to-noise ratio (SNR) greater than 400 in all bands except the green band, indicating that it meets the requirements for water quality monitoring; (2) the semi-empirical estimation model of CChla derived from HJ-2 CCD has a mean absolute deviation (MAD) of 8.18 μg/L, root mean square deviation (RMSD) of 10.66 μg/L and mean absolute percentage deviation (MAPD) of 20.93 %; (3) the higher temporal and spatial resolution of the CCD data enables effective monitoring of water quality parameters characterized by high spatiotemporal variations; (4) HJ-2 CCD exhibits strong consistency with Sentinel-2 MSI and Sentinel-3 OLCI across various bands, with most bands showing correlation coefficients exceeding 0.8 and a MAPD below 30 %. This study reveals the significant potential and practical value of HJ-2 CCD data for monitoring and assessing water quality, providing important information for the design and development of next-generation satellites.